Diseño organizacional para la empresa Ferroamerica de la ciudad de Loja - Iñiguez Sarango, Klever Alexander (2024)
The organizational design is a guide that allows companies to have a correct operation in order to stand out and be more competitive in the market. The present research work, called "Organizational design for the company "Ferroamerica" of the city of Loja", is currently not very competitive because during the period that has been working is managed empirically by the lack of scientific knowledge and ignorance of management processes, therefore objectives were raised that allowed a situational diagnosis of the same in order to build both the business philosophy, organization charts, manual functions, welcome and procedures. The research approach used for its development was qualitative with an exploratory and descriptive type of research, using inductive and analytical methods and an action-research design. The techniques used for data collection were direct observation, an interview with the manager-owner and finally a survey applied to the 6 workers currently working in the company. With the direct observation, the applied survey and the interview it was possible to demonstrate that the company does not have a functional organic structure, all the personnel that conforms it lacks a guide for the development of its activities, it has not been developed induction to the entrance of the same one and there have not been carried out trainings to the personnel. Therefore, the need to develop an organizational design for the company Ferroamerica was born.